Development of Pelubiprofen Tromethamine with Improved Gastrointestinal Safety and Absorption - Ji Yeon Park; Dong Ho Oh; Sang-Wook Park; Bo Ram Chae; Chul Woo Kim; Sang Heon Han; Hyeon Jong Shin; Soo Bin Yeom; Da Yeong Lee; Min Kyu Park; Sang-Eun Park; Jun-Bom Park; et al. (MDPI AG, 2021)
Pelubiprofen (PEL), which is a commercialized non-steroidal anti-inflammatory drug (NSAID), is associated with the risk of gastrointestinal (GI) adverse events following long-term exposure and has poor water-soluble properties. Here, a new pelubiprofen tromethamine (PEL-T) with improved solubility, permeability, GI safety, and absorption, compared to PEL, has been developed. The nuclear magnetic resonance spectroscopy (NMR), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FT-IR) results confirmed that the PEL-T was well formed. The powder of PEL-T showed the presence of additional 6H protons at δ 3.66-3.61 in the 1H NMR spectrum, and shifted the sharp endothermic peaks at 129 °C in DSC, and the spectrum of distinct absorption peaks in FT-IR. In addition, compared with PEL, PEL-T showed a significantly improved solubility in various media and an increased permeability coefficient (Kp) in Caco-2 cells. Furthermore, compared to PEL oral administration, PEL-T was found to significantly reduce the damaged area in an acute gastric damage rat model. The pharmacokinetic study of the PEL-T powder showed higher maximum plasma concentration (Cmax) and area under the plasma concentration-time curve from 0 h to the last time point (AUCt) than those of the PEL powder. Taken together, our data suggest that PEL-T is a recommendable candidate with enhanced gastrointestinal safety and better absorption compared with commercial PEL.